THE QUALITATIVE PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL ACTIVITY OF EIGHT LIBYAN MEDICINAL PLANTS AGAINST PATHOGENIC BACTERIA (مجلة العلوم الإنسانية والتطبيقية, 2018)
The purpose of this study was to investigate the phytochemical and antibacterial activities of eight Libyan medicinal plants including Petroselinum crispum, Eruca sativa, Rosmarinus officinalis, Apium graveolens, Mentha piperita, Thymus capitatus, Punica granatum and Ocimum basilicum. These plants were locally available from different regions in Libya. The leaves of the selected medicinal plants were washed, air dried and then powdered then dissolves in three different solvents which represent the aqueous, methanol and ethyl acetate, the phytochemical screening of samples are showed the presence of the important phytochemical compounds such as Alkaloids, Phenols, flavonoids, saponins, carbohydrate and tannins within most all the plants selected. The antibacterial activities of these plants were evaluated using the agar diffusion method against Staphylococcus aureus, Bacillus subtilis as gram-positive and Escherichia coli, Pseudomonas aeruginosa as gram-negative. The results obtained revealed that not all of the plants were active against the bacteria tested. Over all, the methanolic extract of Punica granatum displayed the greatest antibacterial activity than others. This increased activity may due to the presence of the most active compounds in this plant.Inhibition zone values of the methanol extracts were within the ranges of 9.00 - 36.00 as significantly compared to the ethyl acetate extracts were 9.00-26.00 mm (P < 0.05) and the water extracts which not displayed any activity.